Secondary structure is required for 3' splice site recognition in yeast - Gahura, Ondřej; Hammann, Christian; Valentová, Anna; Půta, František; Folk, Petr (Nucleic acids research, 2011)
Higher order RNA structures can mask splicing signals, loop out exons, or constitute riboswitches all of which contributes to the complexity of splicing regulation. We identified a G to A substitution between branch point (BP) and 3' splice site (3'ss) of Saccharomyces cerevisiae COF1 intron, which dramatically impaired its splicing. RNA structure prediction and in-line probing showed that this mutation disrupted a stem in the BP-3'ss region. Analyses of various COF1 intron modifications revealed that the secondary structure brought about the reduction of BP to 3'ss distance and masked potential 3'ss. We demonstrated the same structural requisite for the splicing of UBC13 intron. Moreover, RNAfold predicted stable structures for almost all distant BP introns in S. cerevisiae and for selected examples in several other Saccharomycotina species. The employment of intramolecular structure to localize 3'ss for the second splicing step suggests the existence of pre-mRNA structure-based mechanism of 3'ss recognition.
Keywords: Molecular Sequence Data; Saccharomyces cerevisiae; Ascomycota; konformace nukleové kyseliny; Nucleic Acid Conformation; Introns; Cofilin 1; fungální RNA; sestřih RNA; Saccharomyces cerevisiae Proteins; Saccharomyces cerevisiae - proteiny; Base Sequence; sekvence nukleotidů; ubikvitin konjugující enzymy; místa sestřihu RNA; Temperature; introny; Ubiquitin-Conjugating Enzymes; molekulární sekvence - údaje; kofilin 1; RNA Splicing; RNA, Fungal; RNA Splice Sites; teplota